Pengukuran Kesiapan Digitalisasi dalam Penghimpunan, Pendistribusian, Pendayagunaan, dan Pelaporan ZIS pada BAZNAS Provinsi Kalimantan Selatan - Mairijani; Sadewa, Manik Mutiara; Pratiwi, Wulan (Indonesian Journal of Applied Accounting and Finance, 2023)
Abstract Entering the Industrial Revolution 4.0, digital technology is an essential part of business line development. This is evident by the decrease in the number of people using the internet; ultimately, social and business organizations must turn to digital media. This study aims to explain how ready digitalization is for the collection, distribution, and reporting of zakat, infaq, and sadaqah in BAZNAS of South Kalimantan Province. Descriptive research using a quantitative approach. Data collection techniques used questionnaires and interviews with amil, especially in the field of ZIS and DSKL collection, distribution, and reporting at BAZNAS of South Kalimantan Province. To calculate the OPZ Digital Readiness Index (IKDZ), the Multi-Stage Weighated Index method was used. The results showed that the collection action received a score of 0.326, the distribution and utilization action received a score of 0.245, and the reporting action received a score of 0.302. Overall, the digitalization readiness level for ZIS and DSKL management reached 0.872, which is at the original digital level and falls into the excellent category.